PENGEMBANGAN INSTRUMEN PENILAIAN MATEMATIKA BERBASIS LITERASI NUMERASI DENGAN PENDEKATAN KONTEKSTUAL KELAS III SD NEGERI 7 LANGSA - Anjani, Siti; Febri Rafli, Muhammad; Maisarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the limited availability of mathematics assessment instruments capable of measuring students' numeracy literacy skills through contextual problems. The assessment instruments commonly used in mathematics learning tend to emphasize computational skills and conceptual mastery, providing limited opportunities for students to apply mathematical concepts to real-life situations. Therefore, this study aimed to develop a mathematics assessment instrument based on numeracy literacy using a contextual approach for third-grade elementary school students and to determine its validity and practicality. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The research subjects included expert validators, a third-grade teacher, and nine third-grade students at SD Negeri 7 Langsa. Data were collected through observations, interviews, validation questionnaires, and response questionnaires from teachers and students. The data were analyzed using descriptive quantitative analysis. The findings revealed that the developed assessment instrument obtained a validity score of 78% from the material expert, categorized as valid, 94% from the evaluation expert, categorized as highly valid, and 100% from the language expert, categorized as highly valid. The practicality test showed a score of 97% based on the teacher's assessment and an average score of 96% based on students' responses, both of which were classified as highly practical. These findings indicate that the mathematics assessment instrument based on numeracy literacy with a contextual approach is valid and highly practical, making it appropriate for use as an alternative assessment instrument in mathematics learning for third-grade elementary school students.